Effects of Stress Relaxation Aging with Electrical Pulses on Microstructures and Properties of 2219 Aluminum Alloy - Tan, Jingsheng (Materials (Basel), 2016)
To realize the high-efficiency and high-performance manufacture of complex high-web panels, this paper introduced electric pulse current (EPC) into the stress relaxation aging forming process of 2219 aluminum alloy and systematically studied the effects of EPC, stress, and aging time upon the microstructure and properties of 2219 aluminum alloy. It is discovered that: (a) EPC greatly enhanced the mechanical properties after stress relaxation aging and reduced the sensitivity of the yield strength for the initial stress under the aging system of 165 °C/11 h; (b) compared with general aging, stress relaxation aging instead delayed the aging process of 2219 aluminum alloy and greatly increased the peak strength value; (c) EPC accelerated the aging precipitation behavior of 2219 aluminum alloy and reduced transgranular and grain-boundary energy difference, thus leading to a more diffused distribution of the transgranular precipitated phase and the absence of a significant precipitation-free zone (PFZ) and grain-boundary stable phase in the grain boundary, further improving the mechanical properties of the alloy.